Strategi Media Relations PT Kimia Farma Diagnostika dalam Mempertahankan Dominasi Pemberitaan Positif di Media Online - Fadlan Praditya; Burhanuddin Burhanuddin; Al-May Abyan Izzy Burhani (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The rapid development of online media has made the internet the primary source of public information, including health information, requiring companies to implement effective communication strategies to maintain a positive image and reputation. PT Kimia Farma Diagnostika, as a healthcare service company, faces challenges in maintaining public trust amid the rapid dissemination of information through online media. This study aims to analyze the implementation of media relations strategies by PT Kimia Farma Diagnostika in maintaining the dominance of positive news coverage in online media. The research employed a descriptive qualitative approach using a case study method through observation, in-depth interviews, literature review, and documentation. The results showed that the company implemented media relations strategies through media relationship management, communication strategy development, and media network expansion. These strategies were carried out through routine communication with journalists, press release preparation, media visits, media monitoring, as well as media selection based on audience segmentation and media relevance. The implementation of these strategies supported the dominance of positive and neutral coverage about the company in online media and contributed to maintaining the company’s reputation amid the increasingly competitive development of digital media.